WHY INTERWAR LITHUANIA DID LOSE VILNIUS AND CONTEMPORARY LITHUANIA LAGS BEHIND ESTONIA? - NORKUS, ZENONAS (Politologija, 2013)
The paper compares the introduction and stabilization of national currency in the First and Second Republics of Lithuania (LR I and LR II) during the years 1918–1922 and 1990–1993, respectively. These diachronic comparisons are supplemented by the synchronic ones where LR I is compared with Estonia, Latvia, and Poland and LR II with Estonia and Latvia. Jointly with Lithuania, all these countries faced the challenge of nation state building simultaneously with the macroeconomic stabilization. Both times, Lithuania was the last to introduce the national currency. The analysis starts with a discussion of the similarities and differences in the economic situations of the LR I and LR II during the first years of independence. In this discussion, the author argues that the prototype of the Soviet command administrative economy was the administrative war economy of Kaiser Germany during WWI, with occupied Lithuania suffering under extreme forms of the administrative control of economic activities by the Oberost authorities. The restoration of the capitalist free market economy and macroeconomic equilibrium was complicated by the extraordinary spending to finance the independence wars in 1918–1920 when national states-in-making lacked administrative capacities to collect taxes in the ordinary ways. Therefore, all Lithuanian neighbours did finance their independence wars by inflation tax, introducing national currencies almost immediately after proclaiming independence and collecting up to 2/3 of the total state revenue from the seigniorage. Among all countries fighting indepenendence wars in the modern times, Lithuania was probably unique in its persistent effort to pay the war cost without the inflation tax. As Lithuania maintained a monetary union with Germany up to 1922, it donated to this country the seigniorage income and was not able to draft all its available manpower because of monetary restrictions. At the same time, the early LR I provides for the posteriority an example of the frugal management of state finance policies even under extraordinary circumstances. This example still lacks the due appreciation by neoliberal monetarist apologists of the sound monetary and fiscal policies. During its early time of restored independence, LR II procrastinated to end the monetary union with its former imperial suzerain (Russia) too for quite a different reason: the choice of the Gediminas Vagnorius’ government to participate in the “inflation race” in the rouble zone after September 1991 when the restoration of independent Lithuania was internationally recognized. The winners in this race were the former republics of the USSR that were the leaders in rising prices and wages. Therefore, while Lithuania in 1918–1922 suffered only from imported (from Germany) inflation, in 1991–1992 this country both imported and exported inflation. While permissive policies of the Vagnorius government helped to void the efforts of the Moscow to undermine Lithuanian independence in January–August 1991 by the economic blockade, their continuation after the dissolution of the USSR delayed the onset of macroeconomic stabilization until the early summer 1993. Even after October 1st, 1992 when the national provisional currency talonas became the only legal tender in Lithuania, its govermnent continued collecting the inflation tax, which was immoral given the absence of the war or other extraordinary circumstances. Because of the delayed macroeconomic stabilization, market reforms in Lithuania were conducted in the wrong sequence, with a large-scale privatization enacted under conditions, near to hyperinflation, which favoured prolonged rent-seeking by the early winners. The correct sequence of market reforms in Estonia, due to its early monetary stabilization (since June 1992), jointly with more favourable initial conditions, helped this country to become the leader in the “Baltic race”. The policy of Gediminas Vagnorius to chase after short-time advantages of the leadership in the inflation race among the former Soviet republics was punished by Lithuania losing the long-time advantages of the leadership in the transformation race among them Baltic countries. According to another concluding causal argument, the governments of LR I committed a strategic blunder by declining to use the inflation tax for the extraordinary spending to finance the independence war in 1918–1920. Despite their smaller populations and a greater WWI damage (in Latvia’s case), both Estonia and Latvia raised more than 70 000 manpower each, financing their war efforts by the inflation tax. Because of its responsible and frugal financial policies, which were wrong given the extraordinary circumstances of a war, the peasantly penny-pinching Lithuania had only some 30 000 manpower at the time of critical battles for its historical capital Vilnius in the autumn 1920. Such military power was too small and weak to hold the city against only one allegedly rebellious division under general Lucjan Żeligowski from landlordly lavish Poland which, like other Lithuania’s neighbours, financed its war effort in 1918–1920 by the inflation tax. So Lithuania lost Vilnius in 1920, because it was not ready to pay its (monetary) price. Credits to Prof. Dr. Arnd Bauerkämper from Freie Universität Berlin who hosted the research visit of the author to Berlin to collect and research part of the sources (about post-WWI inflation in Germany and Eastern Europe) used in the paper.